Collaborative Bilingual Teaching in Turkish EFL Context - Yılmaz, Melda; Dikilitaş, Kenan (My University, 2018)
The aim of this case study is to investigate the way of implication of collaborative bilingual teaching based on co-teaching model between English language teacher and content /class teacher in a private primary level school in Istanbul in the fall term of 2017-2018 academic year and to explore the perceptions and attitudes of the administrators and teachers related to this programme maintained in Turkish EFL context. During the bilingual collaborative teaching, each 1st grade class is staffed by two Turkish native teachers, a monolingual Turkish class teacher and a bilingual English language (L2) teacher, and the medium of instruction is both in the native language, Turkish, and the international language, English. In this study, qualitative research method was used and the data was collected by means of semi structured interviews with 4 administrators and 12 teachers and observations conducted in two classes where co-teaching bilingual education was operated. The data was analysed by means of inductive analysis, a bottom up approach. The analysis of the data revealed out information about the implementation of the programme and the teachers' practises based on different co-teaching roles, administrators and teachers' perceptions including the benefits of the collaborative bilingual education and the challenges faced in this programme and the future actions need to be taken for a successful bilingual education based on collaboration. Thus, the findings were categorized under three main themes: 1) Implementing Collaborative Bilingual Programme and Classroom Practices, 2) Administrators and Teachers' Perceptions, and 3) Future Actions (Actions Need to be Taken).
Keywords: Collaborative Bilingual Education; Turkish EFL Context; Co-teaching